(untitled) (International Journal of Biology and Chemistry, 2014)
This paper discusses the physico-chemical characteristics of a samples of crude oil, gasoline, kerosene and diesel from Zhanazhol oil fields (RK). Zhanazhol oil field is shown to be marked 2.0.1.0 in accordance with the requirements of ST RK 1347-2005 governmental standard. We have found out that the recovered fractions (gasoline, kerosene, diesel fuel) can be used as initial raw materials of motor fuels.